Biocatalyzed Redox Processes Employing Green Reaction Media - Carmen Aranda; Gonzalo de Gonzalo (Molecules, 2020)
The application of biocatalysts to perform reductive/oxidative chemical processes has attracted great interest in recent years, due to their environmentally friendly conditions combined with high selectivities. In some circumstances, the aqueous buffer medium normally employed in biocatalytic procedures is not the best option to develop these processes, due to solubility and/or inhibition issues, requiring biocatalyzed redox procedures to circumvent these drawbacks, by developing novel green non-conventional media, including the use of biobased solvents, reactions conducted in neat conditions and the application of neoteric solvents such as deep eutectic solvents.